Social changes and their impact on sports practice in the school environment - elhadi_aissa; مالكي محمد (sports creativity, 2025)
Social and cultural change has had a major impact on rebuilding the nucleus of Algerian society and its educational institutions. "In the face of all these changes, society must shoulder part of its responsibility to reconsider its value and family structure and all the essential effects "The Algerian society is undergoing a period of great change and this is in all areas especially social and cultural. This change has resulted in several behavioral patterns in the social behavior of individuals, whether in the family or in the various institutions," he said